Options for biological control anaerobic decomposition process - Skliar, Oleksandr; Скляр, Олександр Григорович; Mits, V. (Запоріжжя : ТДАТУ, 2022)
EN: The control of a biological process and its regulation are complex. The purpose of the anaerobic decomposition process in agriculture usually consists in obtaining a constant volume of methane. The most commonly used is a (semi-)continuous mechanically stirred reactor. Continuous production of methane is achieved here if there is a steady state operation. In this case, the changes in the process parameters are equal to zero and the maximum reaction rate possible for the process is achieved [1]. Therefore, parameters such as volumetric load, residence time, achievable degree of decomposition and gas production rate are determined in advance at the stage of plant design and selection of the substrate for processing. The plant operator must ensure that these parameters are kept as constant as possible. However, a steady state regime is not achievable in practice, since problems inevitably arise (for example, changes in the properties of substrates, malfunctions and failure of pumps, supply of disinfectants to the reactor, etc.)
Skliar O., Mits V. Options for biological control anaerobic decomposition process. Технічне забезпечення інноваційних технологій в агропромисловому комплексі : матеріали IV Міжнар. наук.-практ. Інтернет-конференції, м. Запоріжжя, 01-25 листопада 2022 р. Запоріжжя : ТДАТУ, 2022. С. 195-197.